Modeling human mitochondrial diseases in flies - Sánchez-Martínez, Álvaro (Biochim Biophys Acta, 2006)
Human mitochondrial diseases are associated with a wide range of clinical symptoms, and those that result from mutations in mitochondrial DNA affect at least 1 in 8500 individuals. The development of animal models that reproduce the variety of symptoms associated with this group of complex human disorders is a major focus of current research. Drosophila represents an attractive model, in large part because of its short life cycle, the availability of a number of powerful techniques to alter gene structure and regulation, and the presence of orthologs of many human disease genes. We describe here Drosophila models of mitochondrial DNA depletion, deafness, encephalopathy, Freidreich’s ataxia, and diseases due to mitochondrial DNA mutations. We also describe several genetic approaches for gene manipulation in flies, including the recently developed method of targeted mutagenesis by recombinational knock-in.